Utilization of Jengkol Peel (Pithecellobium jiringa (Jack) Prain) as Lead (II) Ions Bio-sorbent with Column Method - Gatut Ari Wardani; Lia Nuramalia; Winda Trisna Wulandari; Estin Nofiyanti (Jurnal Kimia Sains dan Aplikasi, 2020)
Problems arising from laboratory waste include the content of lead metal ions in it, which can affect health. While on the other hand, Jengkol peel is a market waste and has no economic value. Jengkol peel contains hydroxyl groups and carboxylates to bind heavy metals such as lead (II) ions. So, this study aims to determine the effect of variations in flow rate, adsorbent height, and solution acidity and determine the ability of Jengkol peel in adsorbing lead (II) ions in the laboratory liquid by the column method. Organic groups that include active sides can be removed using 1N sodium hydroxide to increase the adsorption ability. Sodium hydroxide functions to dissolve lignin in lignocellulose compounds so that carboxylic groups are formed in cellulose, which has a role in binding metal ions. The determination of functional groups was carried out by Fourier-transform Infrared Spectroscopy. The identification of the adsorbent morphology was carried out by Scanning Electron Microscope. The adsorption of lead (II) ions by Jengkol peel was determined by calculating the difference between the lead (II) ions in the solution after and before passing through the column. The amount of lead metal remaining in solution was determined using Atomic Absorption Spectroscopy. Sodium hydroxide solution with a concentration of 1N can separate lignin from cellulose contained in lignocellulose to enhance the bio-sorbent ability of the Jengkol peel in binding metal ions. The smaller the flow rate in the column, the higher the amount of lead (II) ions adsorbed in the bio-sorbent. The acidity of the solution has the best adsorption at pH 5. The metal ions from the simulation sample can reduce the number of lead (II) metal ions adsorbed by 11%.